Designing and Implementing e-School Systems: An Information Systems Approach to School Management of a Community College in Northern Mindanao, Philippines - Grepon, Benzar Glen S.; Baran, Niño T.; Gumonan, Kenn Migan Vincent C.; Martinez, Aldwin Lester M.; Lacsa, Mona Liel E. (International Journal of Computing Sciences Research; Vol 6 (2022): Vol 6, 2022)
Purpose – Colleges and Universities have been established to provide educational services to the people. Like any other organization, the school has processes and procedures similar to business or industry that involve admissions, processing of data, and generation of reports. Those processes are made possible through a centralized system in storing, processing, and retrieval of data and information, the majority of the schools in the country are already adopting computer-based systems to address their needs especially on their student and school-related transactions. The absence of a computer system and the complexity of the transactions of the college which makes the personnel be loaded with paper works in storing and keeping student records and information is the motivating factor why the School Management Information System has been designed and developed for a community college in the northern part of Mindanao. Method - This paper discusses the Major Functionalities and Modules of the system through its implementation methodology which is the Agile Model and its impact on the delivery of services and procedures in the overall operation of the college. Results – The project has been evaluated based on ISO 25010, a quality model used for product/software quality evaluation systems. Based on the results of the evaluation, SMIS has been Functional, Usable, and Reliable with an average for every criterion above 4.04 indicating very good performance based on a Likert scale descriptive interpretation. Conclusion – Based on the preceding findings of the study, the respondents agreed that the developed e-school system was functional and lifted the transaction process of the school. The faculty and staff have benefited from making use of the system. The overall quality and performance of the system was very good in terms of functionality, usability, and reliability. Recommendations – It is recommended that future development such as the smartphone and tablet-based attendance monitoring should be integrated, a kiosk for grades and schedule viewing should also be placed inside the campus that is connected to the database server. Online student information systems should also be developed for the benefit of the students and parents, in easily monitoring school-related activities and requirements. Research Implications – The study enabled the centralization of school and student data in storing, processing and retrieval. The System has been implemented in the college and has been updated now and then for continuous quality improvement.